Performance in a Pitch Memory Task by Visually Handicapped Children and Youths - Edyta BOGUSZ; Hanna KOPROWSKA; Ewa SKRODZKA (Archives of Acoustics, 2013)
The present work discusses results concerning sound perception obtained in a pitch memorization experiment for blind and visually impaired subjects (children and teenagers). Listeners were divided into two age groups: 7–13 year olds and 14–18 year olds. The study tested 20 individuals (8 congenitally blind and 12 visually impaired) and 20 sighted persons comprising reference groups. The duration of the experiments was as short as possible due to the fact that our listeners were children. To date, no study has described results of such experiment for blind/visually handicapped children and teenagers. In the pitch memory experiment blind teenagers outperformed blind children and both age groups of visually impaired subjects in two out of three tested cases. These results may have implications for the development of auditory training in orientation and mobility of young visually handicapped people.